Unusual Warming in the Coastal Region of Northern South China Sea and Its Impact on the Sudden Intensification of Tropical Cyclone Tembin (2012) - Zhe-Wen Zheng (Advances in Meteorology)
Tropical cyclone Tembin (2012) passed twice and made landfall over south tip of Taiwan in August 2012. During its passage, an unusual sea surface warming was generated at 22.5∘N, 117∘E in the coastal region of northern South China Sea. Subsequently, Tembin passed over this extreme warming region and its intensity was enhanced drastically and suddenly from Category 1 to Category 3 within less than 1-day time interval. This unusual warming seems to largely prompt the intensification of Tembin. Next, the relationship between this extreme warming and rapid intensification of Tembin is identified by atmospheric model Weather Research and Forecast (WRF) with updated time-varying lower boundary condition. In addition, given the tight relationship between generation of unusual warming in the shore region and following possible TC intensification, a series of numerical experiments based on oceanic model Regional Oceanic Modeling System (ROMS) were designed and executed to resolve the possible generated mechanism of the extreme warming. The results indicate that a distinct positive short-wave radiation influx anomaly may dominate the generation of the unusual warming in the shore region during Tembin’s passage. This result is validated by the distributions of free cloudy coverage shown in satellite infrared images.